A law of the iterated logarithm for the product limit estimator with doubly censored data - Messaci, Fatiha; Nemouchi, Nahima (Statistics & probability letters, 2011)
We establish the law of the iterated logarithm for the product limit estimator, when the data are subject to double censoring. This investigation extends the results available for the model for singly censored data.